Conditions for teaching English to young learners: Indonesian teachers’ perspectives - Diah Royani Meisani (English Language Teaching Educational Journal, 2022)
English teachers’ beliefs are one of the captivating topics to study as they contribute the quantity of input for reflection and the enhancement of English teaching and learning. This case study aims at investigating the teachers’ beliefs about the role of exposure, motivation, and practice in English class in elementary school and how they translate their beliefs into routine instructional actions. Semi-structure interviews and classroom observations were conducted to collect the data involving three English teachers at a selected private elementary school in Malang, East Java, Indonesia. The findings show that all of the participants were aware that the role of exposure was essential in learning a foreign language, motivation was a vital factor to achieve the objective of the learning and practice was a central part of proficiency development, and consistent with this, a great deal of effort has been conducted to provide exposure to English, to motivate students, and to create opportunities for students to use English. Hence, the results of the study are expected to give a worthy contribution to teachers of English as a second language, especially at elementary schools and other researchers dealing with exposure, motivation, and practice in learning English.